On surface chemical reactions of free-base and titanyl porphyrins with r-TiO2(110): a unified picture. Issue 21 (18th May 2022) - Schio, Luca; Forrer, Daniel; Casarin, Maurizio; Goldoni, Andrea; Rogero, Celia; Vittadini, Andrea; Floreano, Luca
Abstract : Free-base porphyrins on TiO2 (110) anchor to Obr rows, where they capture diluted hydrogen underneath and favour outdiffusion of Ti interstitials by self-metalation; Ti metalated species may also capture oxygen from hydroxyl adsorbates on Ti5f rows. Abstract : In this Perspective we present a comprehensive study of the multiple reaction products of metal-free porphyrins (2H-Ps) in contact with the rutile TiO2 (110) surface. In the absence of peripheral functionalization with specific linkers, the porphyrin adsorption is driven by the coordination of the two pyrrolic nitrogen atoms of the macrocycle to two consecutive oxygen atoms of the protruding Obr rows via hydrogen bonding. This chemical interaction favours the iminic nitrogen uptake of hydrogen from near surface layers at room temperature, thus yielding a stable acidic porphyrin (4H-P). In addition, a mild annealing (∼100 °C) triggers the incorporation of a Ti atom in the porphyrin macrocycle (self-metalation). We recently demonstrated that such a low temperature reaction is driven by a Lewis base iminic attack, which lowers the energy barriers for the outdiffusion of Ti interstitial atoms (Tiint ) [Kremer et al., Appl. Surf. Sci., 2021, 564, 150403]. In the monolayer (ML) range, the porphyrin adsorption site, corresponding to a TiO-TPP configuration, is extremely stable and tetraphenyl-porphyrins (TPPs) may even undergo conformational distortion (flattening) by partial cyclo-dehydrogenation, while remaining anchored to the O rows up to 450 °C [Lovat et al., Nanoscale, 2017, 9, 11694]. Here we show that, upon self-metalation, isolated molecules at low coverage may jump atop the rows of five-fold coordinated Ti atoms (Ti5f ). This configuration is associated with the formation of a new coordination complex, Ti–O–Ti5f, as determined by comparison with the deposition of pristine titanyl-porphyrin (TiO-TPP) molecules. The newly established Ti–O–Ti5f anchoring configuration is found to be stable also beyond the TPP flattening reaction. The anchoring of TiO-TPP to the Ti5f rows is, however, susceptible to the cross-talk between phenyls of adjacent molecules, which ultimately drives the TiO-TPP temperature evolution in the ML range along the same pathway followed by 2H-TPP.